Whole exome sequencing of thymic neuroendocrine tumor with ectopic ACTH syndrome. Issue 2 (February 2017) - Li, Yanli; Peng, Ying; Jiang, Xiuli; Cheng, Yulong; Zhou, Weiwei; Su, Tingwei; Xie, Jing; Zhong, Xu; Song, Dalong; Wu, Luming; Fan, Liwen; Li, Min; et al.
Abstract : Objective: Thymic neuroendocrine tumor is the second-most prevalent cause of ectopic adrenocorticotropic hormone (ACTH) syndrome (EAS), which is a rare disease characterized by ectopic ACTH oversecretion from nonpituitary tumors. However, the genetic abnormalities of thymic neuroendocrine tumors with EAS remain largely unknown. We aim to elucidate the genetic abnormalities and identify the somatic mutations of potential tumor-related genes of thymic neuroendocrine tumors with EAS by whole exome sequencing. Design and methods: Nine patients with thymic neuroendocrine tumors with EAS who were diagnosed at Shanghai Clinical Center for Endocrine and Metabolic Diseases in Ruijin Hospital between 2002 and 2014 were enrolled. We performed whole exome sequencing on the DNA obtained from thymic neuroendocrine tumors and matched peripheral blood using the Hiseq2000 platform. Results: We identified a total of 137 somatic mutations (median of 15.2 per tumor; range, 1–24) with 129 single-nucleotide mutations (SNVs). The predominant substitution in these mutations was C:G > T:A transition. Approximately 80% of detected mutations resulted in amino acid changes. However, we failed to discover any recurrent mutations in these nine patients. By functional predictions, HRAS, PAK1 and MEN1, previously reported in neuroendocrine tumors, were identified as candidate tumor-related genes associated with thymic neuroendocrine tumors. Conclusions: Using whole exome sequencing, we identified genetic abnormalities in thymic neuroendocrine tumors with EAS. Thereby, this study acts as a further supplement of the genetic features of neuroendocrine tumors. Somatic mutations of three potential tumor-related genes ( HRAS, PAK1 and MEN1 ) might contribute to the tumorigenesis of thymic neuroendocrine tumors with EAS.